VALIDITAS DAN RELIABILITAS MEDIA POSTER UNTUK KEMANDIRIAN BELAJAR SISWA - Buchori, Mochamad Zawahirul; Rukanda, Nandang; Yuliani, Wiwin (IKIP Siliwangi, 2024)
Learning independence is a learning activity from individuals not to depend and rely on others to achieve the goals of learning, besides that learning independence is also one of the factors of successful learning achievement that will be obtained by students. This confirms that appropriate media are needed to support students in increasing their learning independence. The method used in the research is Research and Development (R&D) which aims to develop a product in the form of a learning independence poster. The research results obtained are the product in the form of a learning independence poster that must be revised before being used where the content feasibility aspect gets a good assessment with a decent category, the presentation aspect has points that must be corrected because it gets an inappropriate assessment, while the language aspect gets an assessment in a decent category. That way the product in the form of a learning independence poster can be used as a medium in helping students develop learning independence with notes that must be revised first.